Budgeting nitrogen flows and the food nitrogen footprint of Egypt during the past half century: Challenges and opportunities - Ahmed S. Elrys; Sajjad Raza; Ahmed I. Abdo; Zhanjun Liu; Zhujun Chen; Jianbin Zhou (Environment International, 2019)
Egypt is the largest nitrogen (N) fertilizer consumer in Africa. However, its nitrogen use efficiency (NUE) is low, and the relationships between both dietary options and the NUE trend with reactive N (Nr) release into the environment in Egypt have not yet been studied. In this study, we estimated the changes in the N budget and NUE in Egypt during the past 56 years (1961–2016). We also calculated particular virtual N factors (the average amount of Nr released to the environment during food production per unit of N consumption) for major food items to estimate their N footprints (NF). The total N input to croplands increased from 136 kg N ha−1 y−1 (1961–1970) to 307 kg N ha−1 y−1 (2010–2016), while the total crop N uptake increased from 101 kg N ha−1 y−1 to 136 kg N ha−1 y−1, indicating a decrease of NUE from 71% (1960s) to 44% during 2010–2016. Gaseous N emissions of NH3, N2O, and NO increased from 97, 5.6, and 8.3 Gg N y−1 to 339, 29, and 39 Gg N y−1. The total per capita food NF increased from 15 kg N capita−1 y−1 (1961-1970) to 26 kg N capita−1 y−1 (2010–2016). There was a change in the average per capita food consumption NF and food production NF from the 1960s (3.2 and 11.3 kg capita−1 y−1) to 2010–2016 (5.9 and 20.3 kg N capita−1 y−1). There is a dire need to increase the NUE and decrease the food NF in Egypt to minimize the negative consequences of Nr on the environment. Keywords: Reactive nitrogen, Nitrogen use efficiency, Nitrogen loss, Virtual nitrogen factor, Nitrogen footprint, Egypt